Mapping Research Trends on Physical Fitness Determinants among Physical Education Teachers: A Bibliometric Review of Diet, Physical Activity, Motivation, and Sports Facilities - Wiji Kusrini; Widiastuti; Yasep Seiakarnawijaya (proceedings.icesy, 2026)
Physical fitness is a fundamental component of health and professional performance, particularly for Physical Education, Sports, and Health (PJOK) teachers who are expected to serve as role models for active lifestyles. Despite this expectation, existing studies indicate inconsistencies between professional roles and personal fitness behaviors. This study aims to map global research trends on the determinants of physical fitness using a systematic literature review combined with bibliometric analysis. Scientific articles indexed in the Scopus database and published between 2010 and 2024 were systematically identified and analyzed following the PRISMA guidelines. Bibliometric mapping was conducted using VOSviewer to examine publication trends, keyword co-occurrence, and thematic clusters related to physical activity, dietary patterns, motivation, and sports facilities. The results reveal a steady increase in physical fitness research over the past decade; however, studies focusing specifically on physical education teachers remain limited. Physical activity dominates as the central research theme, while dietary, motivational, and environmental factors appear weakly integrated within existing analytical models. These findings highlight significant conceptual and population-specific gaps in the literature. This study concludes that future research should adopt integrated analytical frameworks that simultaneously examine behavioral, psychological, and environmental determinants of physical fitness, particularly among physical education teachers in urban educational contexts.